2006
DOI: 10.1158/0008-5472.can-06-0734
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Abl Tyrosine Kinases Promotes Invasion of Aggressive Breast Cancer Cells

Abstract: The Abl family of nonreceptor tyrosine kinases consists of two related proteins, c-Abl and Abl-related gene (Arg). Activated forms of the Abl kinases (BCR-Abl, Tel-Abl, and Tel-Arg) induce the development of human leukemia; it is not known, however, whether Abl kinases are activated in solid tumors or whether they contribute to tumor development or progression. Previously, we showed that Abl kinases are activated downstream of growth factor receptors, Src family kinases, and phospholipase C;1 (PLC;1) in fibrob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
247
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(269 citation statements)
references
References 47 publications
21
247
1
Order By: Relevance
“…Further, the facts that c-Abl tyrosine kinase can be activated downstream of EGFR via Src kinase (Plattner et al, 1999) and c-Abl plays a role in breast cancers overexpressing EGFR (Srinivasan and Plattner, 2006) strengthen the possibility of c-Abl contributing to the oncogenicity of NSCLC, especially since our studies show that the deficiency of expression of the functional FUS1 TSG contributes to increased active c-Abl kinase. Further, a recent study has shown that activated Abl kinase has a novel role in the regulation of EGFR endocytosis.…”
Section: Oncogenic Activation Of C-abl In Nsclc J Lin Et Alsupporting
confidence: 60%
See 1 more Smart Citation
“…Further, the facts that c-Abl tyrosine kinase can be activated downstream of EGFR via Src kinase (Plattner et al, 1999) and c-Abl plays a role in breast cancers overexpressing EGFR (Srinivasan and Plattner, 2006) strengthen the possibility of c-Abl contributing to the oncogenicity of NSCLC, especially since our studies show that the deficiency of expression of the functional FUS1 TSG contributes to increased active c-Abl kinase. Further, a recent study has shown that activated Abl kinase has a novel role in the regulation of EGFR endocytosis.…”
Section: Oncogenic Activation Of C-abl In Nsclc J Lin Et Alsupporting
confidence: 60%
“…A recent report has shown that c-Abl tyrosine kinase is activated in aggressive human breast cancer cell lines (Srinivasan and Plattner, 2006). Activation of c-Abl was linked to EGFR expression and activation in the breast cancer cell lines (Srinivasan and Plattner, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In the current study, these cell lines are among those highly sensitive to dasatinib and are classified as post-EMT due to their expression of high levels of vimentin. Also of interest is the observation that the basal cell line MDA-MB-468 was one of only 3 basal cell lines that we found to be resistant to dasatinib and in the study implicating abl this cell line had a low level of abl activation [41]. These data raise the possibility that abl inhibition is another potential mechanism of dasatinib activity in basal breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 66%
“…An alternative explanation for the current results could be based on new data implicating abl in breast cancer. Evaluation of abl activation in a panel of 8 breast cancer cell lines has shown constitutive activation of abl in ''aggressive breast cancer cells'' without increases in abl gene expression [41]. These cell lines included many that were evaluated in our panel, including MDA-MB-468, MCF-7, BT-474, SK-BR-3, MDA-MB-231, MDA-MB-453, and UACC-893.…”
Section: Discussionmentioning
confidence: 99%
“…The activated forms of Abl kinases (BCR-Abl, Tel-Abl and Tel-Arg) induce the development of human leukemia (Skorski et al, 1998;Druker et al, 2001;Pendergast, 2001;Kim et al, 2004). Recent studies suggest that Abl kinases are constitutively activated in breast cancer cells and constitutive activation of Abl kinases promotes breast cancer cell invasion (Srinivasan and Plattner, 2006;Jallal et al, 2007;Srinivasan et al, 2008). Although the mechanism by which BCR-Abl drives leukemiagenesis is well understood, little is known regarding how Abl promotes progression of solid tumors.…”
Section: Introductionmentioning
confidence: 99%